BANK MUAMALAT INDONESIA PROFITABILITY ANALYSIS: STUDY OF THE EFFECTS OF CAPITAL, ASSET QUALITY, EARNINGS AND LIQUIDITY - Sa’idah, Suci Halimatus; Mauluddi, Hasbi Assidiki (Jurnal Ekonomi dan Bisnis Terapan, 2018)
The research aims to know the size of the influence of capital factors, asset quality, earnings, and liquidityytoothe profitability of Bank Muamalat Indonesia either partially or simultaneously. Capital factor is projected by Capital Adequacy Ratio (CAR) ratio, asset quality is projected by Earning Asset Quality (KAP) ratio, earnings are projected by Operational Efficiency Ratio (REO), liquidity is projected by Financing to Deposit ratio (FDR), and profitability is projected by Return On Asset (ROA) ratio. The data used are secondary data from the publication of quarterly financial reports of Bank Muamalat Indonesia. The research model used is multiple linear regression. In determining the result of multiple regression equation estimation to avoid biased, the estimated model is tested by classical assumption. Hypothesis testing usinggtttest toodetermine the effect of partial and F test to determine the effect simultaneously. Next is calculated how big the influence of capital variables, assettquality,eearnings, and liquidityytoothe profitability of Bank Muamalat Indonesia 2007-2017 period. The results showed that capital have no significant effect on profitability, asset quality and liquidity haveaaasignificanttpositive effect on profitability, and earnings have a significant negative effect on profitability